(3VhGHW efM GdGFJeGf GdeUQai (B/ s - (3UdGM GHQGgje TMGJg YWGddgs; (3SejMI eUWai GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3fNdU ef GdHMK Gf VhGHW efM GdGFJeGf cCOGI ef GOhGJ GOGQI GdeNGWQ GdGFJeGfjI HGdHfhc dG JbY JMJ MUQ (B: (3hdG JeKd OQYG jbj GdHfc ef GdJYKQ GdGFJeGfi HTcd cGed hdcf GdGdJRGe HJdc GdVhGHW jLYd GdJYKQ aj GdMOhO GdebHhdI hGdeMOOI SdaG ef bHd GdHfc ai Xd GdXQha GdYGOjI (B.(3ceG GXgQ GdHMK Gf NWI hGVY GdbGfhf aj MeGjI GehGd GdGFJeGf jLH Gf Jchf eMd fXQ NGUI Gf eLQO GeJfGY GdYedGA Yf SOGO GdGehGd GdebJQVI ef GdHfhc dG jcTa Yf eNGdaI LfGFjI JSJhLH GdYbGH GdG GPG TGH GdYdGbI HjfgeG ZT Gh JOdjSs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2008s
(3HHdjhLQGajG(B: (3UaMGJ (B531-542s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdVhGHW GdYGeI ddGFJeGf GdeUQajs; (3GdGFJeGf GdeUQajs; (3eUGOQ GdGFJeGf GdeUQajs; (3GdJTQjYGJ GdGFJeGfjIs; (3GdGYQGa GdGFJeGfjIs; (3JYdjeGJ GdHfc GdeQcRjs; (3GOGQI GdeNGWQ GdGFJeGfjIs; (3eMOOGJ GdbQGQ GdGFJeGfjs; (3GdVhGHW GdNGUI ddGFJeGf GdeUQajs; (3GdJSgjdGJ ebGHd GdVeGfGJ GdYjfjI h GdfbOjI s; (3GdeSFhdjI GdLfGFjI Yf eNGdaI VhGHW efM GdGFJeGf (B((3LQGFe GdHfhc(B)s; (3GdOhQ GdQbGHj ddHfc GdeQcRj Ydj YedjI efM GdGFJeGf s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs